Optimization of alkaline protease production by Bacillus licheniformis MZK05M9 in batch culture using response surface methodology - Mian, Md. Mahmuduzzaman (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.